Table of Content - -, (Journal of medical and pharmaceutical sciences, 2024)
Table of Content:1. The Impact of the Work Environment on the Performance of Nurses in the Saudi Healthcare SectorKhalid mansour althobaiti, Amani Hassan Altherwi, Haya ali almbrook, Abrar fawaz alfayz, Faris Sulaiman aljaloud, Obaid ali alkhairi, ALI HASSAN MOHAMMED ALRASHDI, Badrah Ibrahim Alzubaidi, Abdullah ali hamzah alkhiri, Balker Muhammad Abdullah Alrajhi2. Factors Influencing on Chronic Bacterial Osteomyelitis Recurrence in Shaft of Lower Limb Bones After SurgeryHaitham Al-Ahmer, Fouad Al-Daoud, Gohar Mushtaq, Khaled Emara3. Exploring Risk Factors and Outcomes of Low-Birth-Weight Infants in Misurata Medical Center - A Retrospective Analysis (2022)Salima Mukhtar Elburki, Moktar Ahmed Assadi, Faraj Ali Agdawra, Abdulaleem Ahmed Assadi, Ali Abdulsalam Rajab4. Portulaca oleracea L. (Purslane): Protective Properties against Metabolic Syndrome (A review)Waheeda. E. Ahmed, Arjwan Abdullah Alnoumesi5. Hand Grip and Pinch Strength in a Healthy Children Norms for 6 to 18 Years in Al-Kharj City, Kingdom of Saudi ArabiaDr. Fahd Al-Qaisi6. Effect of diet and dietary habits on Jaws of ancient and modern Population in SudanDr. Razaz Muhammad Siddiq, Prof. Abbas Qaribullah
Keywords: Journal of Medical and Pharmaceutical Sciences